UNFINISHED CHESS GAME: DEMISTIFICATION OF THE FIGURE OF THE VICTIM AND SUBVERSION OF THE DISCOURSE OF RESPONSIBILITY IN THE NOVEL TODAY IS WEDNESDAY BY DAVID ALBAHARI - Rosić, Tatjana (Porównania, 2019)
David Albahari’s novel Danas je sreda (Today is Wednesday) belongs to a group of novels in post-Yugoslav literary production in which – since 2010 – paternity policies have been intensely explored in the context of mechanisms of remembering/forgetting. The paper reviews the narrative strategies of son-narrator testimony by which the stabile identity positions and policies within the complex father-son opposition are disintegrated and and annulled. This disintegration occurs in the process of testifying about the past historical events such as the Informbiro Resolution, the organization of the concentration camp on the Goli otok and the collapse of the SFRY. The father figure also makes the reader face the processes of neoliberal globalization and repatriarchalization, on the one hand, as well as with the necessity of re-examination of the past and establishment of the culture of memory in post-Yugoslav region, on the other. But the fundamental demystification of the figure of the victim – both historical and political – subverts the discourse of responsibility that is established as an already impossible speech in Albaharis novel, branding the post-Yugoslav project of a culture of memory as utopian.